OPERATING CAPACITY, PROFITABILITY, SALES GROWTH MEMENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021:SEBELUM DAN SEMASA PANDEMI COVID-19 - Azhar Shafa Putri Nabila; Vidiyanna Rizal Putri (Ibs Press, 2024)
This study examines the effect of Operating Capacity, Profitability, Sales Growth on Financial Distress. This study compared two periods, namely the period before Covid-19 (2017-2019) and the period during Covid-19 (2019-2021). This study uses data from 21 retail sector companies listed on the Indonesia Stock Exchange. The sampling technique in this study used a purposive sampling technique with predetermined criteria. The research method used in this research is a multiple linear regression analysis technique using E-views 9 software. The results of this study indicate that Operating Capacity has no effect on Financial Distress in the period before Covid-19 (2017-2019) and during Covid-19 (2019-2021). Sales Growth had no effect on Financial Distress in the pre-Covid-19 period (2017-2019), but Sales Growth had a positive effect on Financial Distress during the Covid-19 period (2019-2021). Profitability has a negative effect on Financial Distress in the period before Covid-19 (2017-2019) and during Covid-19 (2019-2021).